Kualitas Produk Dan Lokasi Café Terhadap Keputusan Pembelian (Studi Pada The Eagle Cafe & Resto Kab. Karawang) - Agung Ramdani; Danny Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the effect of product quality and cafe location on purchasing decisions (study at The Eagle Cafe & Resto, Karawang Regency). This research was conducted using quantitative methods with descriptive and verification analysis. The sample in this study amounted to 353 respondents and used a non-probability sampling technique with incidental sampling, which was the determination of the sample based on chance. The data analysis technique used is Likert scale analysis technique and path analysis. Based on the analysis that has been done, this study proves the correlation between the variables of Product Quality and Location obtained a value of 0.931, meaning that both have a strong correlation because the value is positive and the relationship is positive and unidirectional. Partially the effect of product quality on purchasing decisions is 48.3%. The partial effect of location on purchasing decisions is 40.4%, it can be stated that product quality has a greater influence on purchasing decisions than location. The simultaneous effect of Product Quality and Location on Purchase Decisions is 88.4% while the remaining 11.6% is the influence of variables not examined.